1985
DOI: 10.1172/jci111818
|View full text |Cite
|
Sign up to set email alerts
|

Transport of urokinase across the intestinal tract of normal human subjects with stimulation of synthesis and/or release of urokinase-type proteins.

Abstract: Oral administration of clinical-type high molecular weight urokinase (HMW-UK) in a single dose of 30,000-60,000 International Units (IU)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 27 publications
(15 reference statements)
0
18
0
Order By: Relevance
“…The production was confirmed by MULLERTZ et al (1984), but they neglected it because of the small amount involved. However, TOKI et al (1985) estimated a large amount of the production in the blood after oral administration of clinicaltype high molecular weight UK.…”
Section: Discussionmentioning
confidence: 99%
“…The production was confirmed by MULLERTZ et al (1984), but they neglected it because of the small amount involved. However, TOKI et al (1985) estimated a large amount of the production in the blood after oral administration of clinicaltype high molecular weight UK.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has been demonstrated that the active component(s) can be absorbed through the intestinal tract and express their action in the circulation. Nattokinase may induce prourokinase release from liver and thus activate plasminogen in the circulation as suggested for urokinase [5]. In addition, Urano et al [13] demonstrated that their specific nattokinases, subtilisin NAT, inactivated plaminogen activator inhibitor (PAI-1) resulting in enhanced fibrinolysis in vitro.…”
Section: Introductionmentioning
confidence: 98%
“…However, the biological activity of these substances is short lived in the circulation after intravenous administration and there is a significant risk of hemorrhagic complications with a pronounced activation of fibrinolytic activity in whole blood in some circumstances [1][2][3]. Sumi and his colleagues [4,5] were the first to demonstrate fibrinolytic activity in vivo after oral administration of the fibrinolytic enzyme, urokinase. The enzyme was shown to cross the intestinal tract and stimulate systemic fibrinolytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…12) The usage of proteases by oral administration has also been assessed [13][14][15] for the application of proteases to thromy To whom correspondence should be addressed. Tel: +81-538-21-1134; Fax: +81-538-21-1135; E-mail: sugimoto-s@mercian.co.jp Abbreviations: FP, protease from Fusarium sp.…”
mentioning
confidence: 99%